2008
DOI: 10.1128/jb.01513-07
|View full text |Cite
|
Sign up to set email alerts
|

SmdAB, a Heterodimeric ABC-Type Multidrug Efflux Pump, in Serratia marcescens

Abstract: We cloned genes, designated smdAB, that encode a multidrug efflux pump from the chromosomal DNA of clinically isolated Serratia marcescens NUSM8906. For cells of the drug-hypersensitive strain Escherichia coli KAM32 harboring a recombinant plasmid carrying smdAB, structurally unrelated antimicrobial agents such as norfloxacin, tetracycline, 4,6-diamidino-2-phenylindole (DAPI), and Hoechst 33342 showed elevated MICs. The deduced amino acid sequences of both SmdA and SmdB exhibited similarities to the sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…When expressed from plasmids, three additional pumps, SmdAB (a heterodimeric ABC-type), SmfY (an MFS-type) and SsmE (an SMR-type), confer, to a multidrug-susceptible E. coli , resistance to several structurally unrelated antibacterials (Table II). [202204] TetA(41) efflux protein and TetR(41) repressor were observed in an environmental strain of S. marcescens . [205] A TetR/AcrR family repressor PizR, which was identified because of its effect on the production of secondary metabolites (prodigiosin and carbapenem), is a specific repressor of a four-component RND efflux pump, ZrpADBC.…”
Section: Drug Efflux In Gram-negative Bacteriamentioning
confidence: 99%
“…When expressed from plasmids, three additional pumps, SmdAB (a heterodimeric ABC-type), SmfY (an MFS-type) and SsmE (an SMR-type), confer, to a multidrug-susceptible E. coli , resistance to several structurally unrelated antibacterials (Table II). [202204] TetA(41) efflux protein and TetR(41) repressor were observed in an environmental strain of S. marcescens . [205] A TetR/AcrR family repressor PizR, which was identified because of its effect on the production of secondary metabolites (prodigiosin and carbapenem), is a specific repressor of a four-component RND efflux pump, ZrpADBC.…”
Section: Drug Efflux In Gram-negative Bacteriamentioning
confidence: 99%
“…Tetracycline is a substrate for the RND pump SdeXY (68). Matsuo and others showed that the ABC pump SmdAB provided increased tetracycline resistance when it was cloned into a susceptible E. coli strain (257). In addition, the RND pump SdeAB was shown to provide an increase in tetracycline resistance after S. marcescens was exposed to cetylpyridinium chloride (255).…”
Section: Resistance To the Tetracyclines In Serratia Speciesmentioning
confidence: 99%
“…Another efflux pump characterized from S. marcescens, SmdAB, belongs to the ATP-binding cassette (ABC) family (257). When cloned into E. coli, this pump provided elevated MICs for several antimicrobials, including the quinolones ciprofloxacin, norfloxacin, ofloxacin, and nalidixic acid (257). Efflux pumps have not been well characterized for other Serratia species, but several are predicted from the genome sequence of S. proteamaculans strain 568.…”
Section: Quinolone Resistance In Serratia Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new heterodimeric ABC transporter from this microorganism, SmdAB, was cloned, and the plasmid harboring the genes was able to confer resistance to several agents in a hypersensitive strain of E. coli (307). Lactobacillus brevis is a major contaminant in spoiled beer, despite the presence of bacteriostatic compounds derived from the hop plant that are added to beer to give a bitter taste.…”
Section: Vol 72 2008 Bacterial Atp-binding Cassette Systems 343mentioning
confidence: 99%